Features of Postnatal Hippocampal Development in a Rat Model of Sporadic Alzheimer’s Disease - Rudnitskaya, Ekaterina A.; Kozlova, Tatiana A.; Burnyasheva, Alena O.; Tarasova, Anna E.; Pankova, Tatiana M.; Starostina, Marina V.; Stefanova, Natalia A.; Kolosova, Nataliya G. (Frontiers in Neuroscience, 2020)
Aging is the major risk factor of the most common (~95% of cases) sporadic Alzheimer’s disease (AD). Accumulating data indicate that middle age as a critical period for the relevant pathological processes; however, the question of when AD starts to develop remains open. It has been reported only recently that in the early postnatal period—when brain development is completing—preconditions for a decrease in cognitive abilities and for accelerated aging can form. Here, we hypothesized that specific features of early postnatal brain development may be considered some of the prerequisites of AD development at an advanced age. To test this hypothesis, we used OXYS rats, which are a suitable model of sporadic AD. The duration of gestation, litter size, and weight at birth were lower in OXYS rats compared to control Wistar rats. The shortened duration of gestation may result in developmental retardation. Indeed, we noted decreased locomotor activity and increased anxiety in OXYS rats already at a young age: possible signs of altered brain development. We demonstrated retardation of the peak of postnatal neurogenesis in the hippocampal dentate gyrus of OXYS rats. Delayed neuronal maturation led to alterations of mossy-fiber formation: a shortened suprapyramidal bundle and longer infrapyramidal bundle, less pronounced fasciculation of granule cells’ axons, and smaller size and irregular shape of nuclei in the CA3 pyramidal layer. These changes were accompanied by altered astrocytic migration. The observed features of early development may be considered some of the risk factors of the AD-like pathology that manifests itself in OXYS rats late in life.